M. Gorky and the 1935 Discussion About the Writer in Cinematography - Anastasia G. Plotnikova (Studia Litterarum)
Based on previously unknown materials from the Archive of A.M. Gorky and RGALI, the article reveals the history and consequences of the meeting of writers, cinematographers, and composers held on April 10, 1935. With the spread of sound cinema, the verbal part of the cinematographic action began to play a more significant role, which aggravated the issue of “scenario hunger” and the participation of writers in the film process. A significant stage in this discussion was a meeting of artists in the Moscow House of Writers chaired by M. Gorky. The meeting was extremely controversial, and Gorky’s statements were then published in Pravda with the addition of some fragments that aggravated the confrontation. In response, the head of Soviet cinematography B.Z. Shumyatsky sent his article “On the Responsibility of Estimates” to the newspaper, sharply criticizing Gorky. An analysis of the circumstances and consequences of the 1935 conflict suggests that during this period, the struggle between the Union of Soviet Writers and the State Directorate of the Film and Photo Industry intensified not only in aesthetic, methodological, and production aspects but also in matters of ideological and political influence and the distribution of economic resources.